Dietmate: Your Partner in Diabetes Management - Naidu, Kamaleshwahrran; Mohamad Izzat Anis, Eusoff; Pichan, Sandhiya; Gunasegran, Sitha; Syifak, Izhar Hisham (Kolej Komuniti Miri, Sarawak & Unit Penyelidikan dan Inovasi Politeknik, 2024)
Ranking 6th among causes of death in Malaysia, accounting for 1.8% of mortality in 2022, diabetes presents a significant health challenge demanding accessible solutions. In response, Dietmate emerges as a crucial intervention, empowering individuals at risk, those diagnosed, and the public. By offering culturally relevant, personalized meal plans, telehealth consultations facilitated by doctors, dieticians, and physiotherapists, along with comprehensive educational resources, Dietmate addresses the multifaceted aspects of diabetes management. Emphasizing cost-effectiveness, empowerment, accessibility, prevention, and early detection, Dietmate aims to enhance individual health outcomes. Through effective blood sugar management, weight control, and the reduction of complications risk, Dietmate not only improves individual wellbeing but also alleviates the burden on healthcare systems. By combatting the escalating diabetes epidemic in Malaysia, Dietmate paves the way for a healthier future for all Malaysians, promoting a society where proactive health management becomes the norm.